Role of Handgrip Strength as a Predictor of Pulmonary Functions in Subjects with and Without Diabetes Mellitus - SPatil, Shiva Kumar; Bj, Subashchandra (Journal of the Association of Physicians of India, 2022)
Reduction in lung function in diabetics is observed in previous studies. Diabetes-related muscle weakness has been reported previously. The reduced muscle strength in diabetics may also affect the respiratory muscles and contribute to a better understanding of the mechanism behind decreased lung function and its clinical relevance. The objective of this study is to find the association between handgrip strength and pulmonary functions in subjects with and without DM. Case-control study assessing 115 diabetics and 115 nondiabetics of age 18-60 years was done. FBS, PPBS, HbA1c was done to differentiate diabetics and nondiabetics. PFT was performed using spirometry and handgrip strength was measured using an electronic hand dynamometer. Mean handgrip strength among diabetics was 29.3kg (SD 5.23) and among nondiabetics was 32.17kg(SD 8.43). The mean FEV1 in diabetics (2.18 L) was lesser than in nondiabetics (2.37 L). This association was statistically significant with p<0.05. Mean FVC among diabetics (2.63 L) was lesser than in nondiabetics (2.85 L). It was statistically significant with p<0.05. The Pearson correlation coefficient of FEV1 and grip strength among diabetics was found to be positive (r =0.518) and statistically significant (p =0.001). Also, for FVC and handgrip strength, there was a positive correlation (r = 0.49), which was statistically significant(p=0.001). Even in nondiabetics, the Pearson correlation coefficient of FEV1 and grip strength was found to be positive (r =0.633) and statistically significant (p =0.001). Also, for FVC and handgrip strength there was a positive correlation (r = 0.631) among nondiabetics which was statistically significant(p=0.001). Pulmonary function parameters FEV1 and FVC were reduced in diabetics compared with nondiabetics. In diabetics, handgrip strength appears to be reduced compared to nondiabetics. Our study concluded that there is a reduction in lung functions in people with low handgrip strength in both diabetics and nondiabetics.